Math, asked by pjeet5937, 1 year ago

if x= (2/11)^12 ÷(2/11)^10, then Find x^-¹​

Answers

Answered by girl2041
1

Answer:

gxvsbgsnsgbsgjwvwnwbnegenhdndhfnhfnfhfnfnntjrnbtntbtnjtktkyjj4thyjhtjtjtjjyjtjtjjyhyjyjtjrh. e ebnebe Bennn.ebb

Step-by-step explanation:

Dont now............

Follow me then i will give answer

Answered by peddiramakrishna79
3

Step-by-step explanation:

x=(2/11)^12÷(2/11)^10

×=(2/11)^2×(2/11)^10÷(2/11)^10

now (2/11)^10 cancels out

so x=(2/11)^2

then x ^-1

=1/x

1/(2/11)^2

=1/1÷2^2/11^2

=1/1×11^2/2^2

=11^2/2^2

= (11/2)^2

Please dont confuse just i brought denominator up and made it as numerator

hope it helps ..

PLEASE MARK IT AS BRAINLIEST ANSWER..

Similar questions